THE QUALITY OF COFFEE THAT IS PREPARED AND CONSUMED IN THE TRADITIONAL WAY - Natalija Džinić; Marija Jokanović; Božana Odžaković; Slavica Grujić (Journal of Engineering & Processing Management, 2013)
Coffee is one of the most popular beverages worldwide. Consumption of black coffee brew, which is prepared in traditional way is characteristic for this region. Consumer expectations in terms of quality and sensory characteristics of beverages can significantly affect on the acceptability of coffee. The aim of this study was to investigate the quality of roasted ground coffee, that is offered on market (as single sort of coffee and commercial coffee blends) and used for the coffee brews preparation in the traditional way. In order to define the quality of these products, basic chemical composition of roasted coffee samples was tested and the degree of roasting coffee based on the value of the color parameters measured instrumentally was determined. Color, taste, aroma and body of brews prepared from the coffee samples were determined by sensory analysis. Based on the results of chemical analysis of coffee samples, it was found that the quality of the product is in accordance with legislation. Instrumental measurement of color showed that tested coffee samples were dark and medium roasted. Coffee brews were evaluated with relatively high scores for selected sensory properties, depending on the condition of roasting and quality of samples. Color of coffee brew was bright and or characteristic, taste was expressive or characteristic, aroma was characteristic, expressive or very expressive and body of brew was expressive. Coffee brew should have a recognizable body and pleasent aroma. The results of the sensory analysis of the samples showed that black coffee brew quality depends on the degree of roasting, species and sorts of coffee. Based on results from testing of commercial coffee samples quality, it can be concluded that the expected quality coffee brew with specific and pleasent sensory properties and composition can be obtained by proper choice of species and sorts of coffee, their ratio in the blends and continuous control of roasting process and the quality of the product.
Keywords: black coffee; quality; sensory analysis